Slovenski pesniški jezik z vidika jezikovnega načrtovanja do l. 1848 - Stabej, Marko (Slavistična revija, 1998)
Slovene poetic language and the corpus of texts from the first half of the 19th c. have not only an autonomous cultural value, but are also the very beginning of full linguistic functionality and complete textual corpus, as well as a motivation for overcoming diglossia. In this context Kranjska čbelica with Prešeren's poetic opus, which was in the short less succesful from the standpoint of language planning, and Bleiweis' newspaper Kmetijske inrokodelske novice (with Koseski as the most prominent poet), which was in this respect more successfull - are of particular importance. The author explains come reasons for this (from today's canonical value standpoint) seemingly controversial thesis.
Keywords: 1800-1848; pesniški jezik; slovenska književnost; slovenska poezija; slovenščina